Cardiotoxicity of Uremic Toxins: A Driver of Cardiorenal Syndrome - Suree Lekawanvijit (Toxins, 2018)
Cardiovascular disease (CVD) is highly prevalent in the setting of chronic kidney disease (CKD). Such coexistence of CVD and CKD—the so-called “cardiorenal or renocardiac syndrome”—contributes to exponentially increased risk of cardiovascular (CV) mortality. Uremic cardiomyopathy is a characteristic cardiac pathology commonly found in CKD. CKD patients are also predisposed to heart rhythm disorders especially atrial fibrillation. Traditional CV risk factors as well as known CKD-associated CV risk factors such as anemia are insufficient to explain CV complications in the CKD population. Accumulation of uremic retention solutes is a hallmark of impaired renal excretory function. Many of them have been considered inert solutes until their biological toxicity is unraveled and they become accepted as “uremic toxins”. Direct cardiotoxicity of uremic toxins has been increasingly demonstrated in recent years. This review offers a mechanistic insight into the pathological cardiac remodeling and dysfunction contributed by uremic toxins with a main focus on fibroblastic growth factor-23, an emerging toxin playing a central role in the chronic kidney disease–mineral bone disorder, and the two most investigated non-dialyzable protein-bound uremic toxins, indoxyl sulfate and p-cresyl sulfate. Potential therapeutic strategies that could address these toxins and their relevant mediated pathways since pre-dialysis stages are also discussed.